1995
DOI: 10.1523/jneurosci.15-11-07633.1995
|View full text |Cite
|
Sign up to set email alerts
|

Substance P induced by peripheral nerve injury in primary afferent sensory neurons and its effect on dorsal column nucleus neurons

Abstract: Using in situ hybridization and the retrograde tracer, Fluorogold, we examined the expression of preprotachykinin (PPT) mRNA in the rat dorsal root ganglion neurons projecting to the gracile nucleus. Seven days after unilateral sciatic nerve transection, some medium- to large-sized neurons in the rat dorsal root ganglia projecting to the gracile nucleus express PPT mRNA, whereas very few gracile nucleus-projecting neurons on the contralateral side express PPT mRNA. Immunohistochemistry revealed an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(152 citation statements)
references
References 54 publications
9
141
2
Order By: Relevance
“…It should also be noted that unilateral application of chromic gut material alone (Cg) is sufficient to induce bilateral upregulation of substance P in the DRG, suggesting a potential diffusion effect of the inflammatory material of the chromic gut sutures and/or central sensitization. However, nerve root injury has also been reported to reduce substance P when injury-induced behavioral hypersensitivity was produced (Hubbard et al, 2008a;Kobayashi et al, 2004aKobayashi et al, , 2005Noguchi et al, 1995;Rothman et al, 2005;Xu et al, 1996). For example, we have observed decreased substance P in the dorsal horn of the spinal cord and DRG at 7 days following nerve root compression dependent on the presence of mechanical allodynia (Hubbard et al, 2008a,b) and also for the same compression injury used in the current study (Rothman et al, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…It should also be noted that unilateral application of chromic gut material alone (Cg) is sufficient to induce bilateral upregulation of substance P in the DRG, suggesting a potential diffusion effect of the inflammatory material of the chromic gut sutures and/or central sensitization. However, nerve root injury has also been reported to reduce substance P when injury-induced behavioral hypersensitivity was produced (Hubbard et al, 2008a;Kobayashi et al, 2004aKobayashi et al, , 2005Noguchi et al, 1995;Rothman et al, 2005;Xu et al, 1996). For example, we have observed decreased substance P in the dorsal horn of the spinal cord and DRG at 7 days following nerve root compression dependent on the presence of mechanical allodynia (Hubbard et al, 2008a,b) and also for the same compression injury used in the current study (Rothman et al, 2005).…”
Section: Discussionsupporting
confidence: 68%
“…We found that GAP-43 is regulated in peptidergic primary afferent fibers, based on a strong colocalization of GAP-43 and the neuropeptide CGRP. Although CGRP expression can be induced in large A fibers after nerve injury (Malcangio et al, 2000;Michael et al, 1999;Miki et al, 1998;Noguchi et al, 1995), GAP-43/CGRP fibers are most likely small fibers. Indeed, increased spinal GAP-43 expression was not observed in the deeper part of the dorsal horn, typically innervated by large A fibers (Lorenzo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The rats were deeply anesthetized with sodium pentobarbital and perfused transcardially with 1% paraformaldehyde in 0.1 M phosphate buffer (PB), pH 7.4, followed by 4% paraformaldehyde in 0.1 M PB 3, 7, or 14 d after surgery (n ϭ 4 at each time point). The left L4/5 DRGs were dissected out and processed for phosphorylated-ERK (p-ERK) 1/2, p-p38, p-SAPK/JNK, activating transcription factor 3 (ATF3), neuropeptide Y (NPY), neurofilament (NF) 200, glial fibrillary acid protein (GFAP), tyrosine kinase (trk) A, BDNF, and TRPV1 immunohistochemistry according to the procedure used in our previous study (Noguchi et al, 1995). The polyclonal primary antibody for p-ERK1/2 (1:400; Cell Signaling Technology, Beverly, MA), p-p38 (1:400; Cell Signaling Technology), p-SAPK/JNK (1:400; Cell Signaling Technology), ATF3 (1:200; Santa Cruz Biotechnology, Santa Cruz, CA), NPY (1:2000; Amersham Biosciences, Little Chalfont, UK), GFAP (1:400; Dako, Glostrup, Denmark), trkA (1:500; Chemicon), BDNF (1:400; Chemicon), and TRPV1 (1:400; Oncogene, San Diego, CA) and the monoclonal primary antibody for NF200 (1:400; Sigma, St. Louis, MO) were used for DAB staining.…”
Section: Methodsmentioning
confidence: 99%